Comprehensive analysis of novel grafted polyethylenes using multidimensional fractionation methods. Issue 40 (25th September 2018) - Eselem Bungu, Paul S.; Pflug, Kristina; Busch, Markus; Pasch, Harald
Abstract : Noval graft copolymers HDPE- g -LDPE were prepared using a dual reactor setup and characterized regarding molar mass, branching and grafting efficiency using a multidimensional analytical approach. Abstract : Advanced polyolefins exhibit sophisticated molecular structures with unique processing and applications properties. One way of tailor-making novel polyolefin structures is through novel polymerization processes or modifying existing structures through functionalization or grafting. The latter approach is taken in the present work where novel grafted polyethylenes (HDPE- g -LDPE) were prepared. To elucidate the molecular heterogeneity of these novel materials in terms of branching and molar mass, a comprehensive multidimensional analytical approach was developed. Advanced analytical techniques such as CRYSTAF, DSC, HPLC, SEC and NMR were used for bulk sample analysis and first indications for the presence of non-grafted LDPE and HDPE along with the graft polymer HDPE- g -LDPE were obtained. For a more detailed study of the materials' heterogeneity, the samples were fractionated by preparative TREF to obtain fractions which were further analyzed regarding branching, molar mass and crystallinity. Different components including the non-grafted LDPE, HDPE and the grafted HDPE- g -LDPE were identified by crystallization-based, spectroscopic and chromatographic methods. The compositions of the different TREF fractions were estimated and fractions were identified that predominantly consist of HDPE- g -LDPE. The bulk samples and their corresponding TREF fractions were analyzed by 2D-LC (HPLC × SEC) to provide comprehensive two-dimensional pictures demonstrating the relationship between molar mass and branching.